Patients' attitudes towards switching to national volume-based procurement (NVBP) Drugs—a qualitative investigation in Wuhan, China - Tao, Jinyi; Li, Shihong; Xu, Qiling; Gong, Shiwei; Zeng, Fang (BMC health services research, 2023)
The implementation of the NVBP policy has generated considerable reductions in drug procurement prices and an increase in the market share of the NVBP drugs.This study aimed to investigate patients' attitudes towards switching to drugs of national volume-based procurement (NVBP) and identify their underlying influencing factors in Wuhan, China. A total of 21 eligible patients from the Wuhan Union Hospital who were switched to NVBP drugs between January 2022 and May 2022 were included in our study. Semi-structured face-to-face interviews were conducted to collect interview information and the interview data was analyzed by the Colaizzi seven-step method. Twenty-one semi-structured face-to-face interviews were conducted. The duration of each interview was 25-35 min and three themes related to patients' attitudes and their influencing factors were extracted, including (1) Patients' perception of the NVBP drugs; (2) Family and social influence to patients; (3) Medication habits of patients. This study found: 1) 71.4% patients (15/21) showed a positive attitude towards switching to NVBP medicines; 2)80.9% patients (17/21) have felt a significant reduction in their medication cost after the implementation of the NVBP policy; 3)Advices from healthcare professionals and health insurance reimbursement policies showed great impacts on patients' attitude towards switching to NVBP drugs; 4)Attitudes towards switching to NVBP drugs varied considerably among patients with different severities of disease. The implementation of the NVBP policy has significantly reduced the cost of healthcare for patients and has been supported by71.4% (15 of 21) patients. However, some issues have been identified in the implementation of the policy in this study. Health professionals in general need to contribute more efforts to improve patients' preconceptions about the NVBP drugs and boost their confidence in the NVBP drugs.